1994
DOI: 10.1007/bf00932672
|View full text |Cite
|
Sign up to set email alerts
|

Parthenogenesis in the genusSchistosoma: Electrophoretic evidence for this reproduction system inS. japonicum andS. mansoni

Abstract: Mixed infections with Schistosoma japonicum and S. mansoni were carried out in mice. S. japonicum females paired with S. mansoni males developed normally and produced numerous viable eggs; very little sperm was found in the female genital tract. The eggs yielded many miracidia infective to Oncomelania hupensis, the host of S. japonicum. Cercariae arising from miracidia developed into male worms with an electrophoretic pattern of malate dehydrogenase (MDH) corresponding only to the maternal species S. japonicum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Finally, because F1 progeny only harbor the mother genotype, it can only infect the snail corresponding to the mother species (B. truncatus for S. bovis and B. glabrata for S. mansoni). A similar result has been observed in S. japonicum × S. mansoni crosses, where female S. japonicum × male S. mansoni can only infect Oncomelania hupensis snail while where female S. mansoni × male S. japonicum can only infect B. glabrata [36].…”
Section: Resultssupporting
confidence: 82%
“…Finally, because F1 progeny only harbor the mother genotype, it can only infect the snail corresponding to the mother species (B. truncatus for S. bovis and B. glabrata for S. mansoni). A similar result has been observed in S. japonicum × S. mansoni crosses, where female S. japonicum × male S. mansoni can only infect Oncomelania hupensis snail while where female S. mansoni × male S. japonicum can only infect B. glabrata [36].…”
Section: Resultssupporting
confidence: 82%
“…Within the S. haematobium species group, examples of hybridization either in humans or in animals are well documented (Pitchford 1961;Wright & Southgate, 1976;Burchard & Kern, 1985;Kriiger et al 1986;Rollinson et al 1990). Sexual interactions also exist between schistosome species belonging to different groups (Basch & Basch, 1984;Tchuem Tchuente et al 1993;Imbert-Establet, Xia & Jourdane, 1994). With regard to our model, the results showed that in mixed infections of 5. intercalatum and S. mansoni in the same definitive host, there is an homospecific mate preference.…”
Section: Sexual Interactionssupporting
confidence: 50%
“…mansoni × male S . japonicum ) inside mammal hosts [39,40,45]. However, given the propensity of certain schistosome species to form interspecies hybrids [46], it is challenging to distinguish between genetic hybridization and true parthenogenesis.…”
Section: Discussionmentioning
confidence: 99%